Our Point of View at Rehabilitation After Anterior Cruciate Ligament Reconstruction - Zazirnyi, I.M.; Kostrub, O.O.; Kotiuk, V.V.; Plugatar, O.V. (TERRA ORTHOPAEDICA, 2020)
Summary. The article presents rehabilitation program for the patients after anterior cruciate ligament reconstruction. The program is used at the Feofaniya Hospital’s Center of Orthopedics, Traumatology and Sports Medicine and at the Department of Sports and Ballet Injuries of the SI “Institute of Traumatology and Orthopedics of NAMS of Ukraine”. The rehabilitation course is divided on five periods: 1) preoperative period; 2) early postoperative period (acute) (0–2 weeks); 3) function restoring period (up to 9 week); 4) period of preparing and gradual returning to recreation and sports activity (from 9 week); 5) period of returning to full sports activity (after 6–9 months, depending on the type of sport). Principles of postoperative care and rehabilitation in our clinics are as follows: 1) decreasing pain, swelling, and inflammation; 2) full load of the operated on limb with or without crutches; 3) immediate exercises to restore range of motion from 0° to 60–90°, with gradually increase to 120° and full flexion after 6–9 weeks postoperatively (using continuous passive motion; passive, active assisted, and active exercises); 4) exercises for training quadriceps muscle, shin flexor muscles and all lower limb and pelvis muscles, with increasing resistance in close and open kinetic chains; 5) exercises for training proprioception and coordination (from early postoperative period); 6) return to work after 3–6 weeks, health-improvement and sports activity after 4, 6, and 9 months; 7) close cooperation between a surgeon, a rehabilitologist, and a patient during rehabilitation. We focus on achieving the fastest full extension of the knee joint, muscle control and restoration of proprioception. Exercises are performed in closed and open kinetic chains, with muscles tension in the back of the thigh and shin, in the way to avoid too much stress on transplantate. In cases of athletes and recreational active patients, elements of sports specific exercises were included to the rehabilitation program (from early postoperative period). That helped to restore proper patterns of movements and to overcome physical barrier in returning to full sports activity. Return to sport was allowed patients when achieved full range of motion, normal proprioception and balance of muscles; functional tests results were about 90% of the norm and there was no pain or swelling during exercise loads.